Modelling the effects of trees on a contaminated groundwater plume from a gold tailings storage facility in the Orkney district - Grindley, Suzanne (My University, 2015)
The aim of this dissertation was to determine the likely impacts that planting woodlands would have on the storage, transport and discharge of mine water and contaminants, over a plume originating from the West Complex tailings storage facility within the Vaal River mine lease. The hydrological model MIKE SHE was run on a grid comprising of 120m square cells, for a pre-woodland period from 2001 to 2010. Sulphate was used as an indicator of the contaminant plume concentrations and transport across the study area. Six future woodland planting scenarios (2025 to 2034) were then simulated to determine the effects of mature Searsia lancea, Eucalyptus dunnii and Tamarix usneoides, and different planting scenarios on the contaminant plume. Results indicated that planting these deep-rooted species will be effective in decreasing the groundwater levels, groundwater flux and the quantity of contaminants reaching the river. Before tree water and contaminant uptake can be further modelled with improved accuracy within MIKE SHE, the limitations of the use of only one contaminant uptake value for the vegetation needs to be overcome, so that different uptake rates among different tree species can be shown.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. 2014.
Keywords: Mine drainage.; Mine water - Effects of trees on.; Mine water - Environmental aspects.